MINI SOLAR WATER HEATER SEBAGAI PEMANAS AIR BERKELANJUTAN BAGI YAYASAN ODGJ KEMAH PEDULI SAHABAT KASIH - Filian Arbiyani; Christiand; Yeremia Steven Aufey; Julianus Armanda Putra Tarigas; Hadi Sutanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
In daily life, the availability of hot water is essential for supporting health, comfort, and various general activities. Hot water is produced by supplying a certain amount of thermal energy to water until it reaches a desired temperature. This energy is typically derived from sources such as gas, oil, or electricity. At the Kemah Peduli Sahabat Kasih Foundation, the availability of hot water is particularly crucial, as the facility serves individuals with mental health disorders. Basic activities such as bathing, and the preparation of food and beverages, inherently require hot water. The operational funding of the facility relies heavily on donations and social contributions. Therefore, the cost of procuring fuel to ensure the continuous supply of hot water becomes a significant concern and represents a recurring expenditure that demands special attention. To alleviate the financial burden on the foundation's management, a mini solar water heater system utilizing solar energy was designed and developed for use at the Kemah Peduli Sahabat Kasih Foundation. The system primarily consists of temperature sensors, a water storage tank, solar heat-absorbing pipes, and other supporting equipment to ensure proper circulation of hot water. The system was installed at the Kemah Peduli Sahabat Kasih Foundation building located in Cisauk, Tangerang Regency, Banten. This initiative is expected to reduce the foundation’s expenses associated with water heating. Moreover, the presence of this system is anticipated to better support the daily activities of the facility’s residents. Ultimately, the developed water heating system may serve as a model for other similar applications requiring cost-effective hot water solutions.